The Effect of Product Quality and Service Quality on Tourist Satisfaction and Revisit Intention to La Brisa Bali - Ni Luh Putu Erisca Putri; I Wayan Suardana; Ni Ketut Arismayanti (Cita konsultindo, 2024)
La Brisa Bali is a renowned beach club located in the tourist hub of Canggu, Bali. The name